2019
DOI: 10.1096/fj.201900685rr
|View full text |Cite
|
Sign up to set email alerts
|

TMEM70 facilitates biogenesis of mammalian ATP synthase by promoting subunit c incorporation into the rotor structure of the enzyme

Abstract: Biogenesis of F1Fo ATP synthase, the key enzyme of mitochondrial energy provision, depends on transmembrane protein 70 (TMEM70), localized in the inner mitochondrial membrane of higher eukaryotes. TMEM70 absence causes severe ATP‐synthase deficiency and leads to a neonatal mitochondrial encephalo‐cardiomyopathy in humans. However, the exact biochemical function of TMEM70 remains unknown. Using TMEM70 conditional knockout in mice, we show that absence of TMEM70 impairs the early stage of enzyme biogenesis by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 64 publications
6
25
1
Order By: Relevance
“…In addition, we have shown that this is accompanied by a drastic drop in Su.c levels (see Fig. 2-4), which is a unique feature of TMEM70 deficiency and corroborates a very recent report (Kovalčíková et al , 2019). Whether the lack in Su.c was caused by a bioenergetic failure due to the compromised ability of the ATP synthase to assemble in the absence of TMEM70 and/or to the lack of another mitochondrial component(s) whose assembly/stability would be TMEM70-dependent was not known.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we have shown that this is accompanied by a drastic drop in Su.c levels (see Fig. 2-4), which is a unique feature of TMEM70 deficiency and corroborates a very recent report (Kovalčíková et al , 2019). Whether the lack in Su.c was caused by a bioenergetic failure due to the compromised ability of the ATP synthase to assemble in the absence of TMEM70 and/or to the lack of another mitochondrial component(s) whose assembly/stability would be TMEM70-dependent was not known.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the presence of TMEM70 in pull down assays using a FLAG-version of su.c was reported (Kovalčíková et al , 2019), indicating the existence of possible interactions between Su.c and TMEM70. In these assays most of the Su.c pool was immunoprecipitated, which made it difficult to estimate the fraction of Su.c that interacts with TMEM70.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While an MRI conducted was considered normal, the patient was reported to have moderate hypertrophic cardiomyopathy, which is a more common presentation for patients with complex I deficiency (Frazier et al, 2020;Frazier et al, 2019;Gorman et al, 2016;Hanein et al, 2009). Analysis of TMEM126A-interacting proteins revealed an association with TMEM70, a protein long known to play a role in assembly of ATP synthase through incorporation of subunit c into the complex V rotor (Kovalčíková et al, 2019;Spiegel et al, 2011), but more recently also implicated in assembly of the complex I ND4-module (PD-a intermediate) (Guerrero-Castillo et al, 2017;Sánchez-Caballero et al, 2020).…”
Section: Tmem126a Is Important For Biogenesis Of Mitochondrial Complementioning
confidence: 99%
“…The above CNE profiles of ATP synthase indicated possible alterations in supercomplex stability. It is well known, that less stable ATP synthase complexes can be disintegrated during separation at harsher/more stringent conditions of electrophoresis such as upon exposure to Coomassie Blue Dye (Wittig, Meyer et al 2010, Hejzlarova, Kaplanova et al 2015, Kovalcikova, Vrbacky et al 2019). Thus, BNE was further used to assess stability of ATP synthase complexes (Figure 4).…”
Section: Stability Of Atp Synthase Complexmentioning
confidence: 99%